O boom do petróleo e o desenvolvimento humano na Nigéria (1970-2007) - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This study aims to analyze the impacts of oil exploration on human development in Nigeria between 1970 and 2007. The research is grounded in the observation that, although the country experienced a significant increase in oil revenues starting in the 1970s, its social indicators remained low, reflecting persistent inequality in access to essential public services. The investigation is justified by Nigeria’s strategic importance in the global energy landscape and the recurring challenges faced by resource-exporting countries. The methodology employed is qualitative, based on an extensive literature review and documentary analysis, utilizing data from international organizations such as the World Bank and the United Nations Development Programme (PNUD), as well as academic works addressing concepts such as Gross Domestic Product (GDP), the Human Development Index (HDI), the resource curse, and development with freedom. The historical analysis covers different periods of Nigerian politics—including both civilian and military governments—with a focus on how these regimes managed oil revenues. The results demonstrate that the absence of effective public policies, combined with mismanagement, endemic corruption, and institutional weakness, prevented oil wealth from translating into substantial improvements in the population’s living conditions. It is concluded that, in the Nigerian case, resource abundance did not lead to social progress, highlighting the crucial role of institutional quality and governance in achieving human development.
The oil boom and human development in Nigeria (1970-2007)
Keywords: Nigéria; Desenvolvimento humano; Petróleo; Human development; Oil; CIENCIAS SOCIAIS APLICADAS